2022
DOI: 10.21101/cejph.a6740
|View full text |Cite
|
Sign up to set email alerts
|

Travellers' diarrhoea - prevention, trends and role of microbiome

Abstract: Objectives: In this review, we present a contemporary look at the management of travellers' diarrhoea (TD), and we discuss the potential role of a microbiome as well as the administration of live microorganisms in order to prevent TD.Methods: We performed a comprehensive search using the PubMed and Web of Science databases for the period 2014-2021, looking for original and review articles on travellers' diarrhoea.Results: TD belongs among the most frequent illnesses experienced by travellers. For the most part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Mild TD characterizes as 3 unformed stools without other symptoms and does not interfere with the ability of the travelers to continue their activity. In the case of moderate TD, patients suffer from 3 to 5 or more unformed stools a day, without other symptoms, compared to severe TD that consists of more than 5 stools in 24 hours associated with abdominal cramps, fever, vomiting, tenesmus, or blood in feces [129].…”
Section: Infections or Diarrhea Associated With Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mild TD characterizes as 3 unformed stools without other symptoms and does not interfere with the ability of the travelers to continue their activity. In the case of moderate TD, patients suffer from 3 to 5 or more unformed stools a day, without other symptoms, compared to severe TD that consists of more than 5 stools in 24 hours associated with abdominal cramps, fever, vomiting, tenesmus, or blood in feces [129].…”
Section: Infections or Diarrhea Associated With Antibioticsmentioning
confidence: 99%
“…could also be responsible for TD. Recent papers have suggested that enteropathogenic E. coli and enteroaggregative E. coli are more common than enterotoxigenic E. coli-producing heat-labile or heat-stable toxin, which was previously thought to be the most frequent cause of TD [129].…”
Section: Infections or Diarrhea Associated With Antibioticsmentioning
confidence: 99%
“…Intestinal colonization with E. coli is followed by the production of diarrheagenic toxins, such as the Shiga-like toxin produced by EHEC or the heat-labile and the heat-stable enterotoxins produced by ETEC [69]. Enteropathogenic E. coli (EPEC) and EAEC are the most frequently involved pathogens in the development of traveler's diarrhea (TD), a condition with different grades of severity that is defined as three or more unformed stools in a day associated with abdominal pain, vomiting, or fever, which can affect a traveler's activity [71]. C. difficile is a Gram-positive anaerobic spore-forming bacillus present in the intestines of both humans and animals and an important nosocomial pathogen.…”
Section: Diarrheal Illnessesmentioning
confidence: 99%
“…TD has acquired a distinctive significance in occupational settings, as individuals afflicted by TD during their travels are also precluded from participation in daily workrelated activities [6,11,13,14]. Particularly where appropriate medical support may be quite difficult to obtain and rely on because of linguistic and/or infrastructural issues, or even remoteness, Occupational Physicians (OP) may represent key players in implementing an appropriate preventive and on-site management of TD in overseas workers [15][16][17].…”
Section: Introductionmentioning
confidence: 99%